Long-Term Hearing Outcomes Following Stereotactic Radiosurgery in Vestibular Schwannoma Patients—A Retrospective Cohort Study. Issue 4 (20th September 2018) - Santa Maria, Peter L; Shi, Yangyang; Gurgel, Richard K; Corrales, C Eduardo; Soltys, Scott G; Santa Maria, Chloe; Murray, Kevin; Chang, Steven D; Blevins, Nikolas H; Gibbs, Iris C; Jackler, Robert K
Abstract: BACKGROUND: An understanding of the hearing outcomes is needed for treatment counseling for patients with vestibular schwannomas (VS). OBJECTIVE: To determine long-term hearing results following stereotactic radiosurgery (SRS) for VS and identify any influential variables. METHODS: Tertiary hospital retrospective cohort. RESULTS: There were 579 tumors (576 patients) treated with SRS. Eighty-two percent (473) of tumors had ≥1 yr and 59% (344 ≥3 yr follow-up. In the 244 tumor ears, with measurable hearing before SRS who were followed ≥1 yr, 14% (31) had improved hearing, 13% (29) unchanged hearing, and 74% (158) had worsened hearing. In 175 patients with ≥3 yr follow-up and who had measurable hearing pretreatment, 6% (11 ears) improved hearing, 31% (54 ears) unchanged hearing, and 63% (110 ears) had worsened hearing. Patients with tumors with larger target volumes ( P  = .040) and with neurofibromatosis type 2 (NF2; P  = .017) were associated with poorer hearing ( P  = .040). Patients with word recognition scores (WRS) of 50% or poorer had tumors with a larger volume ( P  = .0002), larger linear size ( P  = .032), and NF2 ( P  = .045). Traditionally reported hearing outcomes using the Gardner Robertson maintenance of PTA ≤50 db or WRS ≥50% were 48% at 3 yr, which overestimates hearing outcomes compared to the above reporting standards. CONCLUSION: Hearing declines over time in VS treated with SRS in a high proportion of cases. The frequency and magnitude of long-term hearing decline following SRS argues against prophylactic radiation for small tumors in hearing ears with undetermined growth behavior.